MODERN HYDROGEOLOGİCAL CONDİTİONS OF THE ABSHERON PENİNSULA - NAMAZOV, Ilgar; KARİMOV, Vagif and SHARİFOV, Jafar and PASHAYEVA, Shafagat (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The Absheron Peninsula is the most densely populated and ecologically polluted area in the Republic of Azerbaijan. The rapid development of the oil industry in this area has had a negative impact on both the sea and a significant part of the peninsula. This article examines the physical and geographical conditions, geological and geomorphological structure, and the physico-mechanical properties of rocks from a hydrogeological perspective. By summarizing data on the depth, flow rate, and chemical composition of groundwater and evaluating factors that play a significant role in the formation of the area’s hydrogeological conditions, reasons for the rise in groundwater levels have been established, and solutions for their elimination proposed. The aim of the study is to investigate the causes of ecological imbalance, identify factors affecting the modern hydrogeological conditions of the Absheron Peninsula, and suggest preventive measures against potential geological events. The peninsula’s hydrographic network consists of the Caspian Sea, streams, numerous saline lakes fed by atmospheric precipitation and oil-containing waters, with lakes having a significant impact on the climate and ecological situation in this densely populated area. Methods. Research methods involve studying the physico-mechanical properties of soil and rock samples collected from hand-dug wells and boreholes in terms of engineering hydrogeology, their lithological composition, and thickness. Results. The charachteristics of the artificial lakes, reservoirs, villages, and settlements of the Absheron Peninsula, as well as its unconfined and confined aquifers are studied in the article. Conclusions. The results have revealed the modern hydrogeological conditions across the entire area of the Absheron Peninsula, as well as natural and anthropogenic factors influencing its formation. Based on these factors, it is possible to predict endogenous and exogenous geological events and take appropriate preventive protective measures. Based on the results of preliminary assessment and earlier hydrogeological zoning, 12 promising areas were identified in 3 hydrogeological areas.